2007
DOI: 10.1093/cercor/bhl142
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology of the Koniocellular Axon Pathway in the Macaque Monkey

Abstract: The key objective of this study was to determine the distribution and morphology of koniocellular (K) lateral geniculate nucleus (LGN) axons in primary visual cortex (V1) of the macaque monkey. In particular, we were interested in understanding whether subpopulations of K axons exist in this species and, if so, if these subpopulations arise from different K layers of the LGN. Restricted injections of the tracers, biotinilated dextran amine, or Phaseolus vulgaris leucoagglutinin were targeted to specific LGN K … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 34 publications
6
63
0
Order By: Relevance
“…K layers of the dLGN, especially K3-K6, have been characterized by blue-color processing, and have been shown to project to blobs of V1 (Casagrande et al, 2007;Martin et al, 1997). Since we have revealed that SC1 mRNA is abundantly expressed in blobs as well (Takahata et al, 2009b), our previous studies and this study raise an interesting possibility that SC1 mRNA is selectively expressed in this particular circuitry.…”
Section: Expression Of Occ1-related Genes In Monkey Dlgnsupporting
confidence: 50%
“…K layers of the dLGN, especially K3-K6, have been characterized by blue-color processing, and have been shown to project to blobs of V1 (Casagrande et al, 2007;Martin et al, 1997). Since we have revealed that SC1 mRNA is abundantly expressed in blobs as well (Takahata et al, 2009b), our previous studies and this study raise an interesting possibility that SC1 mRNA is selectively expressed in this particular circuitry.…”
Section: Expression Of Occ1-related Genes In Monkey Dlgnsupporting
confidence: 50%
“…This system has been extensively studied; several reviews describe it in detail (91)(92)(93)(94)(95)(96)(97)(98). Many of the K ganglion cells have bistratified dendritic arbors, as a result of which they receive both ON and OFF inputs from bipolar cells.…”
Section: Other Parallel Channels Originating In the Retinamentioning
confidence: 99%
“…Many cells in the koniocellular division show neurochemical signatures (patterns of immunoreactivity) that are distinct from those of cells in the parvocellular and magnocellular divisions, supporting the koniocellular pathway as a distinct part of the afferent visual stream (Hendry and Yoshioka, 1994;Goodchild and Martin, 1998;Hendry and Reid, 2000;Solomon, 2002;Casagrande and Xu, 2003). It is customarily assumed that ganglion cell input to the koniocellular layers comes from non-midget, non-parasol cells with relatively large ("widefield") dendritic fields and diverse cortical projections (Rodieck and Watanabe, 1993;Hendry and Reid, 2000;Casagrande et al, 2007). The diverse morphological properties of wide-field cells could thus potentially be mapped onto the diverse physiological ("W-like") properties of koniocellular cells (Norton and Casagrande, 1982;Irvin et al, 1986;White et al, 2001;Xu et al, 2001;Solomon et al, 2002;Casagrande and Xu, 2003).…”
mentioning
confidence: 99%